Cryptorchidism in the orl rat is associated with muscle patterning defects in the fetal gubernaculum and altered hormonal signaling - Barthold, Julia S.; Robbins, Alan; Wang, Yanping; Pugarelli, Joan; Mateson, Abigail; Anand-Ivell, Ravinder; Ivell, Richard; McCahan, Suzanne M.; Akins, Robert E., Jr. (Society for the Study of Reproduction, 2014)
Cryptorchidism, or undescended testis, is a common male genital anomaly of unclear etiology. Hormonal stimulation of the developing fetal gubernaculum by testicular androgens and insulin-like 3 (INSL3) is required for testicular descent. In studies of the orl fetal rat, one of several reported strains with inherited cryptorchidism, we studied hormone levels, gene expression in intact and hormone-stimulated gubernaculum, and imaging of the developing cremaster muscle facilitated by a tissue clearing protocol to further characterize development of the orl gubernaculum. Abnormal localization of the inverted gubernaculum was visible soon after birth. In the orl fetus, testicular testosterone, gubernacular androgen-responsive transcript levels, and muscle-specific gene expression were reduced. However, the in vitro transcriptional response of the orl gubernaculum to androgen was largely comparable to wild type (wt). In contrast, increases in serum INSL3, gubernacular INSL3-responsive transcript levels, expression of the INSL3 receptor, Rxfp2, and the response of the orl gubernaculum to INSL3 in vitro all suggest enhanced activation of INSL3/RXFP2 signaling in the orl rat. However, DNA sequence analysis did not identify functional variants in orl Insl3. Finally, combined analysis of the present and previous studies of the orl transcriptome confirmed altered expression of muscle and cellular motility genes, and whole mount imaging revealed aberrant muscle pattern formation in the orl fetal gubernaculum. The nature and prevalence of developmental muscle defects in the orl gubernaculum are consistent with the cryptorchid phenotype in this strain. These data suggest impaired androgen and enhanced INSL3 signaling in the orl fetus accompanied by defective cremaster muscle development.